Quality of life and clinical outcomes of operatively treated patients with flail chest injuries: A multicentre prospective cohort study - Hoepelman, Ruben J.; Minervini, Fabrizio; Beeres, Frank J. P.; van Wageningen, Bas; IJpma, Frank F.; van Veelen, Nicole M.; Lansink, Koen W. W.; Hoogendoorn, Jochem M.; van Baal, Mark. C. P.; Groenwold, Rolf H. H.; Houwert, Roderick M.; , on behalf of the NEXT study group (Frontiers in Surgery, 2023)
INTRODUCTION Most studies about rib fractures focus on mortality and morbidity. Literature is scarce on long term and quality of life (QoL) outcomes. Therefore, we report QoL and long-term outcomes after rib fixation in flail chest patients. METHODS A prospective cohort study of clinical flail chest patients admitted to six level 1 trauma centres in the Netherlands and Switzerland between January 2018 and March 2021. Outcomes included in-hospital outcomes and long-term outcomes, including QoL measurements 12 months after hospitalization. RESULTS Sixty-one operatively treated flail chest patients were included. Median hospital length of stay was 15 days and intensive care length of stay was 8 days. Sixteen (26%) patients developed pneumonia and two (3%) died. One year after hospitalization the mean EQ5D score was 0.78. Complication rates were low and included hemothorax (6%) pleural effusion (5%) and two revisions of the implant (3%). Implant related irritation was commonly reported by patients (n=15, 25%). CONCLUSIONS Rib fixation for flail chest injuries can be considered a safe procedure and with low mortality rates. Future studies should focus on quality of life rather than solely short-term outcomes.